A method of automatic field of view generation and path planning for automated x‐ray inspection - Song, Guiling; Xu, Wei (Expert systems, 2025)
With the increasing accuracy and stability requirements of SMT equipment, automatic x‐ray inspection (AXI) is used as a new popular type of testing technology. First, an imaging constraint model is proposed to ensure that the detected object is not truncated. Second, an improved iterative self‐organizing clustering algorithm was proposed to realize an automatic optimal generation of the field of view and form a Hamiltonian path. Finally, the solution of the shortest Hamiltonian path problem is given by the proposed VTSP heuristic algorithm and VTSP + transformer deep learning algorithm. Experimental results show that, compared with the binary state compression DP method and the local shortest path planning method, the proposed method can support large‐scale nodes, and the performance is improved by 16% on 75 nodes and 31% on 200 nodes. The proposed method achieves a balance between x‐ray imaging efficiency and performance.